Seroprevalence Study of Dengue at a Tertiary Care Hospital in Jaipur, Rajasthan - Ashina Singla; Afreen Ali; Himanshi Galav; Ved Prakash Mamoria (Archives of Medicine and Health Sciences)
Background and Aim: Dengue is one of the most severe mosquito-borne viral infection. In the absence of specific treatments and vaccines for dengue fever (DF), vector control is the only method by which the spread of dengue can be prevented. This study investigates the seroprevalence of DF cases by detecting NS1 antigen and immunoglobulin (Ig)-G and IgM antibody by enzyme-linked immunosorbent assay (ELISA) test. Materials and Methods: This study was carried out in the Department of Microbiology, at a Tertiary Care Hospital, Jaipur (Rajasthan), done between 6 months. Blood samples from clinically suspected cases of dengue were tested immediately for qualitative detection of NS1 Ag, IgM, and IgG antibodies by ELISA. Results: One thousand seven hundred and sixty-three serum samples were tested for dengue NS1 antigen, IgM, and IgG, out of which 1066 were positive for one or more serological parameters. Dengue cases for the NS1 infection are 52.53%, for the IgM infection is 33.39%, and for the IgG infection is 14.07%. Sixty-two percentage positive samples were of male patients and 57% of positive samples were from 19 to 40 years of age group (adult population) (59%). The seasonal trend showed a gradual increase in dengue-positive cases that started in September with a peak in October (46.24%). Conclusion: The monsoon and postmonsoon seasons are times of high virus activity and enhanced vector breeding. The population must thus be constantly monitored to prevent the virus from spreading further, and serological tests are crucial for making an early diagnosis. ELISA is advised for all suspected dengue patients to initiate therapy and decrease the morbidity and fatality rate.